Transdisciplinarity: A New Generation of Architects and Mediocritas - Carta, Silvio (Enquiry The ARCC Journal for Architectural Research, 2016)
The discussion about the legitimacy of architecture being an autonomous discipline or a part of an interrelated system of areas of knowledge has been extensively discussed during the Postmodern period as a tendency of searching for meaning outside of the conventional disciplinary boundaries (Hillier & Leaman 1976; Lefaivre & Tzonis 1984; Hays 1998; Eisenman 2000; Piotrowski & Robinson 2001; Hays & Kogod 2002; Anderson 2002). This article connects the scenario described by Fraser (2005) and Wigley (Stuart 2011) where architecture needs to be considered in an expanded field as consequence of the post-critical period, to the work of a new generation of architects whose interest lies on questions that are peripheral to architecture strictly speaking. The type of architecture that emerges in this scenario is characterised by a proclivity towards other disciplines, including politics, economics and social studies, resulting in a form of design outside of traditional architectural disciplinary boundaries and diluted into a generalised idea. The article presents a series of examples of recent projects and discusses the impact of their approach to architecture, offering a cautionary note. As a conclusion, this paper proposes the notion of mediocritas to establish a right balance between architecture as an autonomous discipline and its disciplinary dislocation with other cultural fields.